Fund Manager Performance in Emerging Market: Factor Specialisation and Financial Crisis Impact. (April 2018) - Galloppo, Giuseppe; Aliano, Mauro
In the branch of literature dealing with analysis of the consistency of management styles, this article investigates the relation between portfolio concentration and the performance of emerging market equity funds. Unlike previous studies, on global and US mutual fund, we focus on emerging markets equity, finding funds with higher levels of tracking error, display lower performance than funds with less diversified portfolios when we do not take into account specific concentration in holdings in different multifactor style. The explanatory power of local models that use local explanatory returns is recently investigated by De Groot, Pang and Swinkels (2012), Cakici, Fabozzi and Tan (2013) and Fama and French (2012). Following the same research line, the most remarkable finding of this article is that the fund-picking process, only based on the level of track error from a broad benchmark, can contribute to disappointing results when it is not also accompanied by information about the fund concentration in multiple market segment. According to the previous work, overall, we found that local factor market model provides quite good representation of local average returns for portfolios formed on size and style factors. The contribution of this research is two-fold. First, we examined emerging market funds from the perspective of active management and second, under the effect of strategies mentioned in Huij and Derwall (2011). Moreover, as additional analysis with respect to most of the previous papers, we also tested the effects of the crisis that we found to have not affected the main result.